The preparation and electrochemical characterization of nanopore array membranes - Sairi, Masniza Binti (Curtin University, 2014)
This thesis aimed to examine the behaviour of nanoscale and microscale liquid interfaces for chemical detection. Nanoporous membranes were prepared by various methods and characterised by ion-transfer electrochemistry at the membrane-modified interfaces between two immiscible electrolyte solutions. The detection of model analytes and ionised drug substances indicate that these miniaturised interfaces provide viable platforms for the detection of ions of chemical and biochemical importance.